2020
DOI: 10.1111/ans.15652
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy withdrawal time and polyp/adenoma detection rate: a single‐site retrospective study in regional Queensland

Abstract: Backgrounds Bowel cancer is the second most common non‐cutaneous cancer diagnosed in Australia among both genders. Colonoscopy withdrawal time of at least 6 min has been accepted as the standard to achieve the target polyp detection rate (PDR) and adenoma detection rate (ADR). A retrospective review was conducted in Bundaberg Hospital to evaluate the relationship between colonoscopy withdrawal time against polyp, adenoma and cancer detection rates. Methods A retrospective study was carried out in Bundaberg Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…By application of conversion factors and comparison to another rural Australian study, it is likely that the ADR in this study is acceptable. 12,13,18 Colonic perforation after colonoscopy is one of the most feared complications. During the data collection period, 2 patients suffered from a perforation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By application of conversion factors and comparison to another rural Australian study, it is likely that the ADR in this study is acceptable. 12,13,18 Colonic perforation after colonoscopy is one of the most feared complications. During the data collection period, 2 patients suffered from a perforation.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9][10] This is consistent with other single-centre quality assurance studies focusing on colonoscopy undertaken in the rural setting. [18][19][20] The completion rate of colonoscopies in this study met targets outlined by various guidelines and professional groups. 4,[7][8][9][10] The completion rate is also similar to those in other Australian studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extremely meticulous bowel preparation is crucial to allow the endoscopic detection of nonpolypoid mucosal lesions [ 76 ]. In addition, an accurate colonoscope withdrawal is crucial and a time longer than 6 minutes has been demonstrated to increase the probability of mucosal malignancy and pre-malignancy detection [ 77 ]. Moreover, a high-definition endoscopy with chromoendoscopy with targeted biopsies of any visible lesions should be performed during surveillance [ 78 ].…”
Section: Diagnosis and Imagingmentioning
confidence: 99%
“…The colonoscopy WT and ADR are widely used quality indicators for colonoscopy performed by trainees (11,24). Multiple studies have shown that a prolonged WT in colonoscopies performed by skilled endoscopists results in a higher ADR (25,26), and a ≥6-minute average WT in negative screening colonoscopies is recommended by the American Society for Gastrointestinal Endoscopy (27). Barclay et al (3) observed a dramatic increase in the ADR for endoscopists with a mean WT >6 minutes compared with those with a WT <6 minutes (28% vs. 12%); the mean WT was 6.3±3.9 minutes.…”
Section: Introductionmentioning
confidence: 99%